Biotechnological techniques in the production of plant-made pharmaceuticals - Balažová, Andrea; Balažová, Ema (De Remediis, 2025)
Plants produce a wide variety of secondary metabolites, many of which have complex structures. Wild and cultivated plants currently remain the primary sources of most pharmaceutically significant secondary metabolites. However, the production of these compounds in plants is limited by the capacity of their biosynthetic pathways. This limitation has prompted efforts to develop methods to increase the yield of desired secondary metabolites. Advances in "omic" techniques have accelerated the development of approaches that utilize plants as bio-factories to produce these valuable compounds. This review provides an overview of strategies for producing high-value plant products and using plants as heterologous hosts to produce foreign recombinant proteins for medical applications.